Preventing ATP Degradation by ASO-Mediated Knockdown of CD39 and CD73 Results in A2aR-Independent Rescue of T Cell Proliferation - Julia Festag; Tamara Thelemann; Monika Schell; Stefanie Raith; Sven Michel; Frank Jaschinski; Richard Klar (Molecular Therapy: Nucleic Acids, 2020)
The adenosine axis contributes to the suppression of antitumor immune responses. The ectonucleotidase CD39 degrades extracellular adenosine triphosphate (ATP) to adenosine monophosphate (AMP), which is degraded to adenosine by CD73. Adenosine binds to, e.g., the A2a receptor (A2aR), which reportedly suppresses effector immune cells. We investigated effects of ATP, AMP, and adenosine analogs on T cell proliferation, apoptosis, and proinflammatory cytokine secretion. CD39 and CD73 expression were suppressed using antisense oligonucleotides (ASOs), and A2aR was blocked using small molecules. Addition of ATP to T cells reduced proliferation and induced apoptosis. Intriguingly, those effects were reverted by suppression of CD39 and/or CD73 expression but not A2aR inhibition. Adenosine analogs did not suppress proliferation but inhibited secretion of proinflammatory cytokines. Here, we suggest that suppression of T cell proliferation is not directly mediated by A2aR but by intracellular downstream metabolites of adenosine, as blockade of the equilibrative nucleoside transporter (ENT) or adenosine kinase rescued proliferation and prevented induction of apoptosis. In conclusion, adenosine might primarily affect cytokine secretion directly via adenosine receptors, whereas adenosine metabolites might impair T cell proliferation and induce apoptosis. Therefore, inhibition of CD39 and/or CD73 has evident advantages over A2aR blockade to fully revert suppression of antitumor immune responses by the adenosine axis.